2022
DOI: 10.1155/2022/1483531
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensively Summarizing What Distracts Students from Online Learning: A Literature Review

Abstract: As online learning becomes an indispensable component of the current education system, students benefit from the advantages of online education. At the same time, students are also facing more challenges during online learning. Multitasking, mind-wandering, and using digital devices are the extensively discussed types of distractions that detriment students’ learning performance by impairing their focused attention. However, the consensus on the definition of distraction and what represents distraction during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 120 publications
(149 reference statements)
1
10
0
Order By: Relevance
“…It is far easier for a learner to be distracted from a screen than from classroom-led instruction (e.g., Aivaz and Teodorescu 2022;Conrad et al 2022). Further, online education permits far more sources of interruption, including phone calls, error messages, text-message alerts, dropped connections, social media notifications, and more (Wang 2022).…”
Section: Interruptions During Digital Learning and Their Consequencesmentioning
confidence: 99%
“…It is far easier for a learner to be distracted from a screen than from classroom-led instruction (e.g., Aivaz and Teodorescu 2022;Conrad et al 2022). Further, online education permits far more sources of interruption, including phone calls, error messages, text-message alerts, dropped connections, social media notifications, and more (Wang 2022).…”
Section: Interruptions During Digital Learning and Their Consequencesmentioning
confidence: 99%
“…Although online learning provides flexibility to students regarding the choice of when, where and how to study, students are easily distracted from their online study (Lodge et al., 2022; Maqableh & Alia, 2021). More specifically, distractions can be defined as attention being diverted from the primary task to secondary tasks (Wang, 2022). Distracted learning can adversely affect student learning (Schmidt, 2020).…”
Section: Student Engagementmentioning
confidence: 99%
“…Digital devices typically refer to electronic tools such as smartphones and tablets that are used for leisure purposes (Flanigan & Kim, 2022). Since online learning occurs mainly in students' homes rather than in traditional classrooms under the watchful eye of the instructors, students find it harder to maintain focused attention during online lessons (Wang, 2022). A recent study found a significant difference between online and face‐to‐face learning modes, with a whopping 95% of students saying that they used their devices in online courses for non‐course related purposes, compared to 75% in face‐to‐face classes (Aivaz & Teodorescu, 2022).…”
Section: Student Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the basis of these findings relies upon whether the overall learning execution is engaging or if the learner has distractions interfering with their online environment. Some opinions from learning blogs weigh in on the latter: Surrounding distractions impact overall learning outcomes [48,49]. Other results show that if the learning professional is not proficient, online users will likely fail the learning objective compared to their physical classrooms [50,51].…”
Section: Learning Professionals' Ratings In Online Environmentsmentioning
confidence: 99%